Development of binder based on phosphogypsum hardening by mixed type - T. А. Bakhtina; N. V. Lyubomirskiy; A. S. Bakhtin; G. R. Bilenko; I. A. Tyunyukov (Vestnik MGSU)
Introduction. Creation of waste-free technologies for production of low-energy building materials and products involving recycling of secondary raw materials is one of the priority areas of economic development in most countries. In this regard, the urgent task is to develop competitive binders based on phosphogypsum with the addition of hydrated lime by designing rational compositions of phosphogypsum-lime compositions hardening by mixed type.Materials and methods. Waste phosphogypsum from Titanium Investments LLC, Armyansk, was used as a secondary sulfate-containing raw material. Hydrated lime for research was obtained by slaking lump lime produced in shaft furnaces of the lime workshop of Crimean Soda Plant JSC, Krasnoperekopsk. Analysis of the mineralogical composition of phosphogypsum and artificial stone based on it was carried out using synchronous TG-DTA/DSC thermal analysis on an STA 8000 analyzer (Perkin Elmer). The dispersed composition of phosphogypsum and hydrated lime was determined by laser diffraction using a Partica LA-960 laser particle size analyzer (Horiba). The determination of the mechanical characteristics of the prototypes was carried out on the basis of the MCC8 control console (Controls).Results. The results of the development of compositions based on phosphogypsum-lime compositions showed that after forced carbonization of these compositions for 180 minutes in an air-gas environment with a 50 % CO2 concentration, it is possible to obtain a water-resistant stone material (Kr 0.78–0.8) with strength at compression 28–32 MPa, average density 1,750–1,780 kg/m3 and water absorption by mass and volume of 11–15 and 19–26 %, respectively.Conclusions. Probably, additional optimization of the conditions of obtaining samples (pressure, water content of the mixture, introduction of filler), the regime of forced carbonate hardening (hardening time, CO2 concentration) will further improve the studied properties of the resulting stone material. The obtained experimental data suggest that, based on the proposed binder, it is possible to produce a certain range of small-piece wall products, taking into account additional scientific research in this area.